Student Organization Strategies and Challenges in Instructing Grammar for Students’ Daily Communication: A Study of Language Institution: Student Organization Strategies and Challenges in Instructing Grammar for Students’ Daily Communication: A Study of Language Institution - Silfiyah Hikmatul Maulidah; Durratul Hikmah (Journal of Innovative and Creativity, 2025)
This study investigates the strategies and challenges faced by the NATO student organization in instructing grammar to support students' daily English communication at the Foreign Language Development Institute (FLDI) of Nurul Jadid Islamic Boarding School. Using a descriptive qualitative approach with semi-structured interviews and non-participant observations, the study identifies three instructional strategies: structured explanation and direct correction, communication-based instruction, and a blended approach. The main challenges encountered include low student interest and difficulty integrating grammar into everyday communication. These findings highlight the potential of peer-led instruction in non-formal educational settings.